Raman study of the substrate influence on graphene synthesis using a solid carbon source via rapid thermal annealing. (26th July 2019) - Bleu, Yannick; Bourquard, Florent; Loir, Anne‐Sophie; Barnier, Vincent; Garrelie, Florence; Donnet, Christophe
Abstract: We report the results of a comparative investigation of graphene films prepared on Si(100) and fused silica (SiO2 ) combining pulsed laser deposition and rapid thermal annealing using Ni catalyst. The effect of modifying the substrate and/or growth temperature (600–1, 000°C) of graphene synthesis was investigated by Raman microspectroscopy mapping. Graphene grown on Si(100) was multilayered, and various nickel silicide phases had formed underneath, revealing dependence on the growth temperature. Films prepared on SiO2 mainly comprised bilayered and trilayered graphene, with no traces of nickel silicide. Analysis of Raman D, G, and 2D peak intensities and positions showed that modifying the growth temperature had different effects when a Si(100) or a SiO2 substrate is used. These findings advance our understanding of how different combinations of substrate and thermal processing parameters affect graphene synthesis from solid carbon source using nickel as a catalyst. This knowledge will enable better control of the properties of graphene film (defects, number of layers, etc.) and will have a high potential impact on the design of graphene‐based devices for scientific or industrial applications. Abstract : We performed a comparative study of graphene films prepared on Si(100) and fused silica (SiO2 ) combining pulsed laser deposition and rapid thermal annealing using Ni catalyst. Raman microspectroscopy mapping shows that graphene grown on Si (100) was multilayered and various nickel silicide phases had formed underneath, revealing dependence on the growth temperature, whereas the films prepared on SiO2 mainly comprised bilayered and trilayered graphene, with no traces of nickel silicide.